Liberalism without Democracy Nationhood and Citizenship in Egypt, 1922-1936 - Maghraoui, Abdeslam M. (Politics, History, and Culture, 2006)
The history of Western intervention in the Middle East stretches from the late eighteenth century to the present day. All too often, the Western rationale for invading and occupying a country to liberate its people has produced new forms of domination that have hindered rather than encouraged the emergence of democratic politics. Abdeslam M. Maghraoui advances the understanding of this problematic dynamic through an analysis of efforts to achieve liberal reform in Egypt following its independence from Great Britain in 1922.In the 1920s and 1930s, Egypt's reformers equated liberal notions of nationhood and citizenship with European civilization and culture. As Maghraoui demonstrates, in their efforts to achieve liberalization, they sought to align Egypt with the West and to dissociate it from the Arab and Islamic worlds.